Multidirectional leg asymmetry assessment in sport - Hewit, J.; Cronin, J.; Hume, P. (Strength and Conditioning Journal, 2012)
Leg asymmetry assessments in athletes can provide valuable prognostic/diagnostic information. This brief review provides information on outcome measures that describe limb asymmetry (power, force, and distance/height jumped), reliability of single-limb multidirectional assessments, and expected magnitudes of asymmetry in noninjured and injured athletes. The reliability (coefficient of variation = 2.8-40%, intraclass correlation coefficient = 0.80-1.0) of single-limb multidirectional leg assessments allows strength and conditioning coaches to use these assessments to detect asymmetries in athletes, which may provide information about the potential for injury and hence guide injury prevention programming. Expected magnitudes of limb asymmetry are less than 15% for noninjured athletes.